Método heurístico para el aprendizaje de problemas de inecuaciones en los estudiantes del primer año de bachillerato general unificado de la sección vespertina del colegio de bachillerato Pío Jaramillo Alvarado de la ciudad de Loja, periodo 2016-2017 - Yunga Salinas, Jose Geovanny (2017)
The present investigation refers to the heuristic METHOD FOR LEARNING PROBLEMS OF INEQUALITIES IN THE STUDENTS OF THE FIRST YEAR OF SECONDARY SCHOOL GENERAL UNIFIED OF THE EVENING SECTION OF THE COLLEGE BACCALAUREATE PIO JARAMILLO ALVARADO OF THE CITY OF LOJA, period 2016-2017, has as general objective to optimize the learning of inequalities through the application of the heuristic method in the first year of secondary school general High School College unified Pio Jaramillo Alvarado of the city of Loja, period 2016-2017, for the fulfillment of this goal was met with the following phases: Comprehensive, diagnostic, modeling, implementation and assessment of the heuristic method through the Wilcoxon sign rank test to assess the Effectiveness of the learning problems of inequalities which could present difficulties in learning. With the completion of the investigation it was confirmed that students have difficulties in the resolution of problems of inequalities, also, that the application of the heuristic method enables students to develop the ability to solve problems of inequalities which facilitates their learning. However through the application of the heuristic method in an appropriate manner to the improvement of the learning problems of inequalities in the first year of high school evening unified general section of the Pío Jaramillo Alvarado school